Relative carrier-envelope phase dependence of resonant propagation of two-colour femtosecond pulses in V-type atomic medium - 谭霞 王振东 王蕾 樊锡君 (Chinese physics B, 2010)
Using numerical solution of the full Maxwell-Bloch equations, which is obtained by the finite-difference time-domain method and the iterative predictor-orrector method, we investigate the modulation effect of relative carrierenvelope phase （hereinafter referred to as the relative phase） on resonant propagation of two-colour femtosecond ultrashort laser pulses in a V-type three-level atomic medium. It is found that the pulse splitting occurs for a smaller value of relative phase; when the value of relative phase increases to a certain value, only the variation of pulse shape is present and the pulse splitting does not occur any more; moreover, when the value of relative phase is smaller, the pulse group velocity is larger. The relative phase also has an obvious effect on population and spectral property. Different population transfers can be realized by adjusting the value of relative phase. Generally speaking, for the pulses with smaller areas their spectral strengths and frequency ranges decrease obviously with the value of relative phase increasing; for the pulses with larger areas, with value of the relative phase increasing, their spectral strengths decrease remarkably but the relative strengths of the higher frequency components increase significantly, while the spectral frequency range is not varied evidently.